A Systematic Review of Cognitive Impairments Associated With Kidney Failure in Adults Before Natural Age-Related Changes. (22nd November 2018) - Brodski, Julia; Rossell, Susan L.; Castle, David J.; Tan, Eric J.
Abstract: Objectives: Recognition of cognitive impairment in chronic kidney disease (CKD) and its impact on functioning in adults is growing. The vast majority of studies to date have been conducted in older populations where CKD is more pronounced; however, the degree to which age-related cognitive changes could be influencing these findings remains unaddressed. This current study thus aimed to review cognitive impairment findings by stage in non-elderly CKD samples.Methods: PubMed and Medline via Scopus were searched for cross-sectional or cohort studies and randomized controlled trials that assessed cognitive function in individuals with CKD in any research setting. CKD studies including patients at any illness stage were included providing participants were below 65 years old, were not on peritoneal dialysis and had not undergone a kidney transplant.Results: Fifteen studies, with a total of 9304 participants, were included. Cognitive function broadly deteriorated from stage 1 to stage 5. Early stage CKD was associated with a drop in speed of processing, attention, response speed, and short-term memory abilities. Moderate stage CKD was associated with deficits in executive functioning, verbal fluency, logical memory, orientation and concentration. People with end stage kidney disease manifested significant deficits in all previous cognitive domains, along with cognitive control, delayed and immediate memory, visuospatial impairment, and overall cognitive impairment.Conclusions: Cognitive impairment is evident across the stages of CKD, independent of age-related changes, for both lower-order and higher-order cognitive abilities. These impairments also increase between the stages, suggesting a cumulative effect. Future directions for research are discussed. ( JINS, 2019, 25, 101–114)